Methodological Approaches to Mapping your Shopping Discounts (Economic journal of Lesya Ukrainka Volyn National University, 2016)
In the article the economic substance of discounts as part of the marketing pricing policy, the main aim of discounts. The analysis and assessment of methodological approaches trade discounts, based on the nature of their origin. The necessity of introducing analytical accounts of income which detail the operation of goods with discounts.Studied ways to improve the accounting of discounts on trade, and proposed to specify accounting in formation for opening sub-types of the company. The proposed order of the accounting discounts the company will enable grouping based on additional analysis and correlation of discounts and sale to choose their system.